Isolation, identification and characterization of plastic degrading Gut bacteria from Zophobas atratus larvae - Zaman, Ifthikhar (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2024.